2007
DOI: 10.1099/mic.0.2006/002154-0
|View full text |Cite
|
Sign up to set email alerts
|

First report of Mycobacterium bovis DNA in human remains from the Iron Age

Abstract: Tuberculosis has plagued humankind since prehistoric times, as is evident from characteristic lesions on human skeletons dating back to the Neolithic period. The disease in man is due predominantly to infection with either Mycobacterium tuberculosis or Mycobacterium bovis, both members of the M. tuberculosis (MTB) complex. A number of studies have shown that when conditions permit, surviving mycobacterial DNA may be amplified from bone by PCR. Such ancient DNA (aDNA) analyses are subject to stringent tests of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 36 publications
5
101
1
3
Order By: Relevance
“…Recent molecular studies on mycobacterial DNA demonstrated TB infection in the old spinal remains of the ancient Egyptian mummies and the Iron Age [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Recent molecular studies on mycobacterial DNA demonstrated TB infection in the old spinal remains of the ancient Egyptian mummies and the Iron Age [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Back pain is the most frequent presenting symptom of spinal tuberculosis [7]. Early diagnosis and prompt treatment are necessary to prevent permanent neurological disability and to minimise spinal deformity [8,9]. Plain radiographic changes associated with spinal TB such as destruction of the inter-vertebral disk space and the adjacent vertebral bodies, collapse of the spinal elements, formation of a 'cold' abscess around the lesion and anterior wedging leading to kyphosis and gibbus formation are seen relatively late [2,10].…”
Section: Resultsmentioning
confidence: 99%
“…However, no M. bovis was found. Indeed, there has only been one reported case of human tuberculosis associated with M. bovis aDNA (Taylor et al, 2007). This was found in a small group of pastoralists in south Siberia, dating from approximately 1761 to 2199 years BP, placing the remains within the Iron Age period.…”
Section: Recent Findings and Increased Understandingmentioning
confidence: 99%